Early assessment of forest restoration techniques using chlorophyll fluorescence and diagnosis of oak (Quercus ilex sub. ballota) seedlings vitality - Ceacero, Carlos J; Díaz-Hernández, José L; D del Campo, Antonio; Navarro-Cerrillo, Rafael Mª (BOSQUE, 2017)
Chlorophyll a fluorescence has been applied to study the evolution of leaf photoprotection processes to dissipate excess absorbed energy that can not be fully utilized in photochemical reactions, and reflects the plants ability to adapt to environmental conditions. Plants environmental conditions can be modified by forest restoration techniques to ensure successful seedlings establishment, hence chlorophyll a fluorescence can be a useful tool for assessing plant response to planting stress. The objective of this paper was to analyze the chlorophyll a fluorescence as an early indicator of oak seedling response to the establishment stress and as a useful tool for the assessment of different competition control and individualized protection techniques (tillage, herbicide, mulch, tree shelter) used in forest restoration. A field experimental plot with these restoration treatments was established and a monthly monitoring of chlorophyll a fluorescence and a vitality analysis were carried out between August 2003 and October 2004 on oak seedlings. Results showed that fluorescence parameters were sensitive to stress conditions prevailing in each analysed period. On the evaluation of herbaceous competition control techniques, no significant results on the chlorophyll a fluorescence were observed. However, tree shelters exercised a protection effect on seedling limiting the photoinhibition processes during spring and winter periods. Finally, protected plants showed major photochemical efficiency than that showed by unprotected ones according to vitality tests. Therefore, the chlorophyll a fluorescence analysis was proved to be a useful tool for early assessment of oak seedlings establishment stress and for the assessment of certain forest restoration techniques, such as those that combine control of herbaceous competition and individualized seedling protection.